Utilization of Materials "Academic Arapça" for Listening Skills in Arabic Language Education - Jannah, Nur Aini Sholihatun; Nurhidayati, Nurhidayati; Ahsanuddin, Mohammad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Istimâ' Ibtidâ'i course in the Arabic Language Education Department at the State University of Malang refers to the Al-‘Arabiyyah baina Yadaik material only in the form of learning audio. The aims of this study were to: 1) use the material “Academic Arapça” to improve listening skills of undergraduate students in Arabic Language Education Department, and 2) improve listening skills in undergraduate students of Arabic language after using the material “Academic Arapça”. The method research is a classroom action research with quantitative data processing. The results from this research can be concluded that the learning outcomes of students in listening learning obtained an average pretest score of 71 .57 and a post-test of 94.47. Furthermore, the result from the N-Gain is in the high category with a percentage of 81, 18%, which show an increase in results in the use of “Academic Arapça” for the special learning process of the Arabic language department.